Land and water use changes in the US–Mexico border region, 1992–2011. (26th October 2018) - Bohn, Theodore J; Vivoni, Enrique R; Mascaro, Giuseppe; White, Dave D
Abstract: The linkages between land and water use are often neglected when considering resource management. Here, we examined regional changes in land and water use along the US–Mexico border in the decades following the North American Free Trade Agreement, using bi-national land cover maps from 1992–2011, a process-based hydrology and irrigation model driven with long-term meteorological data, and agricultural production and urban water demand statistics. During the study period, land and water use in the region partially re-oriented around the needs of US cities, leading to crop to urban conversions and water savings in the US, while agricultural and urban expansion in Mexico resulted in local aquifer exploitation and reduced river flows. We identified that land uses with lower rates of water consumption (urban in US and agriculture in Mexico) expanded more than those with higher demands (irrigated agriculture in US and urban in Mexico) due to the water scarcity in the region. This resulted in divergent trends in the US and Mexico that in aggregate has led to an unsustainable trajectory in land and water resources.